"NANOTECHNOLOGIES AND THEIR SIGNIFICANCE IN ENVIRONMENTAL PROTECTION" - Xusniddinov Faxriddin Shamsiddinovich (Web of Journals Publishing, 2024)
Nanotechnology is a extremely wide term referring to the very minute particles which are used for the various purposes such as medicines, textiles, robotics, paint industry and various other fields, Nanotechnology may become the most demanded technology in the current and future world as it has immense potential, it have evolved in many different forms for example nanotechnology when used with in the field of medicine it open a wide area of avenue which is unexplored and can benefit many people in several ways like imaging, sensing, targeted drug delivery, and gene delivery systems, and artificial implants, Nanotechnology may become the most demanded technology in the current and future world as it has immense potential, nanotechnology may revolutionize the field of medicine as it can reach to the deepest part of the body with very little or no side effect, nanorobots the results of biotechnology may eliminate the cause of disease even before it appears on large scale in the body, it has the power to improve the quality of medicine and increase the overall health of the common person, nanotechnology in the field of medicine will be the boon to the mankind if the technology is carefully utilized.
Keywords: nanotechnology, nanoparticle, nanomedicine, drug delivery system.